Conteúdo de óleo e proteína bruta nos grãos e correlações com algumas características agronômicas de linhagens e variedades de soja - Gonçalves Fontes, Luiz; de Almeida Filho, José; Silva Reis, Múcio; Sediyama, Tuneo; S Sediyama, Carlos (Revista Ceres, 2025)
The performances of 13 soybean genotypes, grown in Capin6polis and Viçosa, Minas Gerais, were analyzed in relation to oil and protein content in the seeds and their correlations with days to flowering, days to maturity, and grain yield.